Understanding the Role of Sustainable-Oriented and Process Innovation With Lean Practices in Achieving Sustainability Paradigm: A Chinese Perspective - Liu, Guodong; Ding, Yuan; Wen, Chen; Gao, Ke; Wang, Tao; Sun, Ruiqi (Frontiers in Environmental Science, 2022)
The organizational development following the philosophy of sustainability is becoming the prerequisite for companies, which urges and emphasizes them to incorporate social, economic, and environmental aspects into their manufacturing and operations. Despite plethora of researches exploring lean practices as the solution for improving productivity, it is limited to the operational aspects only, thus ignoring the other aspects of sustainability. Moreover, there is a dearth of studies that explored the combined effect of sustainable innovation, process innovation, and lean practices on the three aspects of sustainability. The current study is an attempt and contribution in the existing literature through the sample of 431 respondents from ISO 14001 certified Chinese organizations during COVID-19 pandemic conditions. The estimations were performed through the Partial Least Squares–Structural Equation Modeling. The results revealed a positive association among the proposed hypothesis of aforementioned studied phenomena. In addition, the current study explores the role of sustainable innovation as a mediator between lean and three dimensions of the sustainability, which is reportedly found to be a partial mediator as both direct and indirect effects are found to be statistically significant. Through the findings of the current study, the managers and decision makers can comprehend the potential of the possible benefits which can be reaped by incorporating both lean and sustainability within their operations.